Markerless analysis of swimmers` motion: a pilot study - Ceseracciu, E.; Sawacha, Z.; Fantozzi, S.; Dona, G.; Corazza, S.; Gatta, G.; Cobelli, C. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Regular laboratory-based motion analysis with skin surface markers is not always feasible. In particular, when studying swimmers kinematics, traditional motion capture techniques cannot be adopted. Although video recordings from swimmers often exist, current methods for biomechanical analysis of these are inadequate. They usually rely on manual digitization of joints` position on a single sagittal view of the subject. Therefore, in this study a method for three dimensional (3D) markerless motion capture of swimmers is presented. The method adopts the markerless motion capture system developed at Stanford University.